2021
DOI: 10.1093/ofid/ofab035
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Health Care Administrative Diagnosis Codes to Identify Nontuberculous Mycobacteria Disease: A Systematic Review

Abstract: Background Health care administrative database research frequently uses standard medical codes to identify diagnoses or procedures. The aim of this review was to establish the diagnostic accuracy of codes used in administrative data research to identify nontuberculous mycobacterial (NTM) disease, including lung disease (NTMLD). Methods We searched Ovid Medline, Embase, Scopus, Cochrane Database of Systematic Reviews, Cochrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Multiple studies have demonstrated the limitations of using diagnostic billing (International Classification of Diseases [ICD]) codes to identify rates of NTM disease. Barriers include lack of clinician familiarity with NTM diagnostic characteristics and variable rates of need for active antimicrobial therapy, which might not be necessary for treatment of NTM lung disease, unlike for many other infectious diseases ( 20 , 21 ). Several additional recent studies have evaluated laboratory-based surveillance of NTM, including 1 study from a CDC surveillance program ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated the limitations of using diagnostic billing (International Classification of Diseases [ICD]) codes to identify rates of NTM disease. Barriers include lack of clinician familiarity with NTM diagnostic characteristics and variable rates of need for active antimicrobial therapy, which might not be necessary for treatment of NTM lung disease, unlike for many other infectious diseases ( 20 , 21 ). Several additional recent studies have evaluated laboratory-based surveillance of NTM, including 1 study from a CDC surveillance program ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cases in this study were selected based on the presence of a single diagnostic code for NTM. Prior studies attempting to validate the use of diagnostic codes in identifying NTM cases have demonstrated that the presence of a diagnostic code for NTM has moderate sensitivity but a very high positive predictive value (PPV) for identifying a true case 33. Attempts to add further qualifiers to the search such as the use of fluoroquinolones within a specific time range of the diagnosis code served to improve PPV only somewhat but further decreased sensitivity 34.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies attempting to validate the use of diagnostic codes in identifying NTM cases have demonstrated that the presence of a diagnostic code for NTM has moderate sensitivity but a very high positive predictive value (PPV) for identifying a true case. 33 Attempts to add further qualifiers to the search such as the use of fluoroquinolones within a specific time range of the diagnosis code served to improve PPV only somewhat but further decreased sensitivity. 34 When the literature review is expanded to include those studies assessing pulmonary NTM disease alone, the use of a single diagnosis code to identify cases becomes more commonplace.…”
Section: Discussionmentioning
confidence: 99%
“…There are inherent limitations in retrospective claims-based epidemiologic studies, including variations in coding practices and the potential for coding inaccuracy (overcoding, undercoding, miscoding) [ 6 , 46 ]. Case ascertainment methodology similar to that used in our investigation has reported a positive predictive value of 72% and a sensitivity of 42% for identifying NTMLD among patients with bronchiectasis, supporting that this method is valid for identifying NTMLD; the relatively low sensitivity suggested that NTMLD was often underdiagnosed or miscoded in claims-based epidemiologic research [ 35 ].…”
Section: Discussionmentioning
confidence: 99%